The Posttraumatic Impact of Recurrent Pregnancy Loss in Both Women and Men - Kuhlmann, Emily; Scharli, Pauline; Schick, Maren; Ditzen, Beate; Langer, Laila; Strowitzki, Thomas; Wischmann, Tewes; Kuon, Ruben-J. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Recurrent pregnancy loss is usually associated with significant psychological distress for both partners of the couple. It may act as a traumatic experience resulting in a posttraumatic stress disorder. The object of this study is to examine the posttraumatic impact of recurrent pregnancy loss on men and women and their interdependencies.Methods Cross-sectional study. All couples referred to the special unit for recurrent pregnancy loss between March 2019 and October 2020 were asked to participate with a sample size of 105 couples and 17 women. They were invited to complete a questionnaire package estimating the prevalence of posttraumatic stress, with anxiety, depression, lack of social support and dysfunctional coping strategies as contributing risk factors. Couple data were analysed with the Actor Partner Interdependence Model, taking the couple as a dyad.Results The response rate was 82.3 percent, with posttraumatic stress being measured in 13.7% of the women versus 3.9% of the men (p = 0.017). For women, number of curettages, controlled for the number of losses, correlated with the severity of posttraumatic stress (p < 0.05). Higher levels of anxiety, depression and lack of social support in women correlated positively with posttraumatic stress in their partners. The men’s coping strategy “trivialization and wishful thinking” as well as “avoidance” correlated with more severe posttraumatic stress in the female partners (both p < 0.05).Conclusion The posttraumatic risks within a couple with recurrent pregnancy loss are interdependent. Recurrent pregnancy loss clinics should assess posttraumatic risks of both partners in their routine diagnostic process.
Keywords: wiederholte Spontanaborte; posttraumatischer Stress; Geschlechterunterschiede; emotionaler Stress